Burgess on D.H. Lawrence [videorecording] - Burgess, Anthony; Freeman, Jill (Profile of a writer, 1985)
Briefly surveys the life of the English writer and analyses of his major works. Burgess traces the influence of the small, narrow-minded mining town where Lawrence grew up. He presents also his own appraisal of the novelist whose explicit views on sex made him a controversial figure in the 20th century.